The Paradox of Justice in the Free Nutritious Meal Program - Shintia Lailatul Firdaus; Siti Dwi Astuti (Mimbar Keadilan, 2026)
The Free Nutritious Meal Program, initiated under Presidential Regulation No. 83 of 2024 concerning the National Nutrition Agency, represents a strategic government policy aimed at improving children’s nutritional quality as part of fulfilling the right to health guaranteed under Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, in practice, the implementation of MBG has generated serious problems, including mass food poisoning incidents affecting more than 7,000 students across various regions. This article employs a juridical-normative approach. The findings reveal that the absence of a regulatory framework—given that the implementation of MBG relies solely on internal technical guidelines of the National Nutrition Agency without a binding legal basis equivalent to a Presidential Regulation—has resulted in a normative vacuum, weakened food safety standards, and the lack of an emergency legal response mechanism. Such conditions amount to violations of the right to health, the right to food safety, and social justice. From the perspective of justice theory, although MBG was intended as an instrument of distributive justice, substantively it fails to deliver fairness and capability, instead creating new vulnerabilities for marginalized groups, particularly children. Moreover, the involvement of military and police apparatus in the management of the Free Nutritious Meal Program undermines the system of checks and balances in public administration, rendering MBG a concrete example of policy failure that erodes the principle of social justice.